Peran Lingkungan Keluarga Dalam Mendukung Kemampuan Menyimak Anak Sekolah Dasar - Ni Made Diana Wulandari (Prodi PGSD Unsultra, 2023)
Listening is an early language skill mastered by humans. Listening skills become the basis for other language skills. Human life first learns to listen, after that learns to speak, then reads and writes. Listening is always used in everyday life, both in the family, school and community environments. However, most elementary school children don't like listening because they think that listening is boring. However, the important role of skill mastery or listening ability is very visible in the school environment. At school, most students spend time listening to the lessons delivered by their teachers. So as parents, they have an important role in supporting their children's listening skills so that they can understand the lessons they follow during their time at school